2014
DOI: 10.1038/srep07169
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of Mycobacterium iranicum UM_TJL against representative mycobacterial species suggests its environmental origin

Abstract: Mycobacterium iranicum is a newly reported mycobacterial species. We present the first comparative study of M. iranicum UM_TJL and other mycobacteria. We found M. iranicum to have a close genetic association with environmental mycobacteria infrequently associated with human infections. Nonetheless, UM_TJL is also equipped with many virulence genes (some of which appear to be the consequence of transduction-related gene transfer) that have been identified in established human pathogens. Taken all together, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…M. iranicum has been isolated in various regions including Iran; the Mediterranean (Italy, Greece); Northern Europe (the Netherlands, Sweden); the United States; and Asia (Malaysia, Japan). [7], [8], [9] It is a newly discovered species, with the first documented case reports dating back to 2005[3]. Prior to the publication of this current report, M. iranicum was isolated in both immunocompetent patients and those with immunocompromising conditions, including renal transplantation, cancer, diabetes mellitus, Crohn's disease, and human immunodeficiency virus (HIV) infection (Table 1).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…M. iranicum has been isolated in various regions including Iran; the Mediterranean (Italy, Greece); Northern Europe (the Netherlands, Sweden); the United States; and Asia (Malaysia, Japan). [7], [8], [9] It is a newly discovered species, with the first documented case reports dating back to 2005[3]. Prior to the publication of this current report, M. iranicum was isolated in both immunocompetent patients and those with immunocompromising conditions, including renal transplantation, cancer, diabetes mellitus, Crohn's disease, and human immunodeficiency virus (HIV) infection (Table 1).…”
Section: Discussionmentioning
confidence: 97%
“…In a comparative genome analysis, M. iranicum was found to have a close genetic association with other environmental mycobacteria. [8] Based on phylogenetic analysis, M. iranicum may be closely related to another rapid grower M. gilvum . [9] It may have acquired virulence genes via horizontal transfer with other mycobacteria, Gram-positive bacteria ( Rhodococcus, Corynebacterium, Nocardia ), and Gram-negative bacteria ( Achromobacter ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CoNS are typically benign inhabitants of the human skin and mucous membranes, but they are associated with infections and can be pathogenic to humans with compromised immune systems [ 10 ]. Mycobacterium iranicum is a newly described species which has been isolated from clinical specimens originating in diverse countries including Iran , Greece , the Netherlands , Sweden and the USA [ 11 ], although genomic comparison indicated that this is likely an environmental bacterium [ 12 ]. Pseudomonas oryzihabitans (synonym Flavimonas oryzihabitans ) has been isolated from water and damp environments such as rice paddies and sink drains [ 13 ].…”
Section: Introductionmentioning
confidence: 99%